Clipperton, seul territoire français dans l’océan Pacifique nord-oriental : quels enjeux environnementaux et géopolitiques ? - Anthony Tchékémian (Études Caribéennes)
Clipperton or Passion Island is a French possession, located in the north-eastern Pacific Ocean. Uninhabited since 1945, the atoll is considered the most isolated in the world. In addition to a few plant and animal species that thrive there, the island has large colonies of seabirds, land crabs and recently rats, which are engaged in an interspecific struggle. In addition, Clipperton's EEZ provides a significant resource of fish and polymetallic nodules. A scientific expedition studied the remains present on the coral crown: from Mexican remains from phosphate mining, to those abandoned by the American army, to wrecks of fishing boats, to the numerous pieces of waste transported by marine currents. The problem of such remains is thus considered not only as a reverse side of production, but also as a research object combining historical, geographical, economic, geopolitical, landscape and symbolic dimensions. Indeed, the island of Clipperton, currently free of human settlement and occupation, is nevertheless subject to anthropic interactions. In addition to the fact that its location gives it a geostrategic interest for the French State, the island constitutes an in situ and in vivo laboratory, for long-term scientific study.